Pesticide Labeling: Signal Words - Frederick M. Fishel (EDIS)
This document interprets signal words seen on pesticide labels and discusses the toxicity criteria used in determining the appropriate signal word for the pesticide. Examples of typical statements found on pesticide labels which convey information to the handler of the product are provided. This document is PI-100, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date February 2006.